أثر المتغيرات الديموغرافية على مؤشرات رأس المال البشري في الجمهورية العربية السورية - حيدر عز الدين; إبراهيم عمار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aims to study the evolution of demographic variables and the human capital indicators in the Syrian Arab Republic, design a mathematical model for linking demographic variables and human capital, and analyze the effect of demographic variables on human capital. The development of the variables of the study, and the design of a model to study the relationship between demographic variables and human capital indicators, using the Canonical Correlation, and the use of SPSS V23, and reached the following main results: The demographic variables affect The variables of human capital by 98.7%. There is a positive effect of the following variables: fertility rate and infant mortality rate under five years and qualitative balance in the legal compound, while the following variables: crude death rate and life expectancy at birth for females negatively in the legal compound, as it influences the human development index and the percentage of students graduating from universities Public and private and the percentage of graduate students graduating from public universities positively in the legal compound, while the variables affect the enrollment rate to university education and unemployment rate negatively legal compound, and that 47.5% of the difference In human capital variables, it is due to the change in demographic variables, and 55.7% of the variation in demographic variables is due to the change in human capital indicators. هدف البحث إلى دراسة تطور المتغيرات الديموغرافية في الجمهورية العربية السورية, ودراسة تطور مؤشرات رأس المال البشري في الجمهورية العربية السورية, وتصميم نموذج رياضي للربط بين المتغيرات الديمغرافية ورأس المال البشري, وتحليل أثر المتغيرات الديمغرافية على رأس المال البشري, واعتمد الباحث على المنهج الوصفي التحليلي لدراسة تطور متغيرات الدراسة, وتصميم نموذج لدراسة العلاقة بين المتغيرات الديمغرافية ومؤشرات رأس المال البشري وذلك باستخدام الارتباط القانوني, وتم الاستعانة ببرنامج SPSS V23, وقد توصل إلى أهم النتائج التالية: أن المتغيرات الديموغرافية تؤثر بمتغيرات رأس المال البشري بنسبة 98.7%. يوجد أثر إيجابي للمتغيرات التالية: معدل الخصوبة ومعدل وفيات الرضع دون الخمس سنوات والتوازن النوعي في المركب القانوني, بينما تؤثر المتغيرات التالية: معدل الوفيات الخام والعمر المتوقع عند الولادة للإناث سلباً في المركب القانوني, كما أنه تؤثر المتغيرات دليل التنمية البشرية ونسبة الطلاب المتخرجين من الجامعات الحكومية والخاصة ونسبة طلاب الدراسات العليا المتخرجين من الجامعات الحكومية بشكل ايجابي في المركب القانوني, بينما تؤثر المتغيرات نسبة الالتحاق إلى مرحلة التعليم الجامعي ومعدل البطالة سلباً بالمركب القانوني, وأنّ نسبة 47.5% من التباين الحاصل في متغيرات رأس المال البشري يعود سببه إلى التغير في المتغيرات الديموغرافية, وأن نسبة 55.7% من التباين الحاصل في المتغيرات الديمغرافية يعود سببه إلى التغير في مؤشرات رأس المال البشري.